Fatores estressores de pais de uma unidade de terapia intensiva neonatal - Kegler, Jaquiele Jaciara (2018)
A cross-sectional study realized with the objective of analyzing the factors associated with the stress of parents of neonates hospitalized in a Neonatal Intensive Care Unit. The study participants were the father or the mother, or both, of newborns hospitalized in a Neonatal Intensive Care Unit of a public hospital in the central region of Rio Grande do Sul. To collect the data, the Parental Stress Scale: Neonatal Intensive Care Unit (PSS: NICU) was translated and validated for the Brazilian population and an instrument for the characterization of the participants. Data analysis was performed in the R program through descriptive and analytical statistics, testing the association between stress and sociodemographic variables of parents and of birth and newborns' clinics. The study followed Resolution 466/2012 and has ethical approval. Of the 204 participants, it was found that they were female (62.3%), aged between 26 and 35 years (41.2%), lived in a stable union or with a partner (67.2%), had a son (45.6%) and had a high school education (27.9%). They came from the central-west macroregion (92.1%) in the state of Rio Grande do Sul. The socioeconomic strata were C2 (23.5%) and D-E (23.5%). The occupation that obtained the highest percentage was from the home (28.6%). 13.7% of the parents had previous experience with hospitalization of a child in the Neonatal Intensive Care Unit. The change in the role of mother/father was the subscale in which the highest level of stress was obtained (mean=3.49) and the items considered more stressful by the parents in this subscale were "Separated from my baby" (mean=4.00) and "Feeling helpless and unable to protect my baby from pain and painful procedures" (mean=3.78). The Cronbach alpha obtained for PSS: NICU was 0.92 in metric 1 and 0.93 in metric 2. The subscales that make up the PSS: NICU also presented values of Cronbach's alpha considered to be reliable, between 0.77 and 0.88. The sociodemographic variables associated with higher levels of stress were female, had no previous experience with neonatal unit, higher education and had religion. Among the clinical variables of newborns, hospitalization in the high-risk unit, respiratory support, use of two intravenous devices, previous surgical procedure, sedation and use of a bladder catheter are mentioned. It was concluded that the hospitalization of a child in a neonatal unit is a stressful experience for the parents and that there are sociodemographic and neonatal factors that contribute to increase this stress. Therefore, it is necessary professional’s reflect about their practices as well as the reformulation of these, so that the integration of the family occurs in the care and, thus, can minimize the suffering of the parents.